500. Efficacy of 30-Day Fidaxomicin for Treatment of Acute Clostridium difficile Infection With History of Multiple Recurrences. (26th November 2018) - Lee, Christine; Habib, Minahz; Kim, Christiana; Goldeh, Peyman; Abouanaser, Salaheddin; Kim, Peter
Abstract: Background: Multiple recurrent Clostridium difficile (mrCDI) infections pose major challenges to patients and to the healthcare system. mrCDI is associated with multiple, prolonged hospitalizations and significantly higher costs. It can also lead to chronic, severe diarrhea, colectomy, or death. Fecal microbiota transplantation (FMT) is an effective treatment, but its long-term safety remains unknown, and approximately 10% of patients do not respond to multiple FMTs. A 30-day course of fidaxomicin was evaluated for treatment of acute episode of CDI superimposed on mrCDI, including those who did not respond to multiple FMTs. Fidaxomicin was chosen because it disrupts the fecal microbiome less than vancomycin. Methods: Twenty-nine adult patients with at least two episodes of recurrent CDI were initiated on fidaxomicin 200 mg when they experienced new episode of CDI (symptoms plus positive for CD toxin gene by polymerase chain reaction). These patients continued with fidaxomicin 200 mg twice daily for 10 days, and 200 mg once daily for 20 additional days in an open-label clinical trial. The primary endpoints were a clinical response at the completion of 30-day course of fidaxomicin and a sustained clinical response at week 8 from the last dose of fidaxomicin. Patient health-related quality of life was evaluated throughout the treatment using the RAND-36 Item Health Survey (copyright© the RAND Corporation). Results: Twenty-four of the 29 patients (83%) experienced clinical resolution of CDI-related symptoms at the completion of 30-day fidaxomicin treatment. Twenty-two of the 29 patients had a sustained clinical response with the overall cure rate of 76% (22/29). Eleven of the 29 patients had multiple FMTs and were enrolled into this study as they failed FMTs. Eight of the 11 patients (73%) of these patients had a sustained clinical response. Statistically significant improvements ( P < 0.05) in multiple domains of quality of life according to the RAND-36 Item Health Survey were also observed. Conclusion: An extended regimen of fidaxomicin is an effective treatment for adults with multiple rCDI and in restoring quality of life, including those who failed FMTs. Disclosures: C. Lee, Rebiotix: Board Member and Grant Investigator, Consulting fee and Research grant. Merck: Research Contractor, Research grant. Pfizer: Grant Investigator, Research grant. Seres: Grant Investigator, Grant recipient. P. Kim, Rebiotix: Board Member, Consulting fee.